2018
DOI: 10.1016/j.dadm.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

The personalized Alzheimer's disease cortical thickness index predicts likely pathology and clinical progression in mild cognitive impairment

Abstract: Introduction An Alzheimer's disease (AD) biomarker adjusted for age-related brain changes should improve specificity for AD-related pathological burden. Methods We calculated a brain-age-adjusted “personalized AD cortical thickness index” (pADi) in mild cognitive impairment patients from the Alzheimer's Disease Neuroimaging Initiative. We performed receiver operating characteristic analysis for discrimination between patients with and without cerebrospinal fluid evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 47 publications
(67 reference statements)
0
38
0
Order By: Relevance
“…In this study, we aimed to answer these questions using the cortical thickness data extracted from T 1 -weighted MR scans, deep neural network classifier, and transfer learning. Cortical thinning has been reported in AD/MCI patients (Du et al, 2007; Lerch et al, 2008; Lerch et al, 2005; Singh et al, 2006), and has been identified as imaging biomarkers for the identification of AD/MCI, as well as the progression from MCI to AD (Querbes et al, 2009; Racine et al, 2018; Schaerer et al, 2016). However, a substantial body of existing studies (Eskildsen et al, 2013; Wee et al, 2012) employed regional features, e.g., the mean cortical thickness within a region-of-interest (ROI), for classification, but did not incorporate the cortical geometry.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we aimed to answer these questions using the cortical thickness data extracted from T 1 -weighted MR scans, deep neural network classifier, and transfer learning. Cortical thinning has been reported in AD/MCI patients (Du et al, 2007; Lerch et al, 2008; Lerch et al, 2005; Singh et al, 2006), and has been identified as imaging biomarkers for the identification of AD/MCI, as well as the progression from MCI to AD (Querbes et al, 2009; Racine et al, 2018; Schaerer et al, 2016). However, a substantial body of existing studies (Eskildsen et al, 2013; Wee et al, 2012) employed regional features, e.g., the mean cortical thickness within a region-of-interest (ROI), for classification, but did not incorporate the cortical geometry.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of our study was to identify the structural cortical thickness difference among AD, aMCI-m, aMCI-s and NC groups by both ROI-based and vertex-based methods. Based on previous studies on AD and aMCI subjects [21, 17], we hypothesized that both aMCI-m and aMCI-s groups might have significant cortical thickness decrease comparing to NC group, while AD group would be more likely to exhibit cortical thickness decrease than both aMCI-m and aMCI-s groups. In addition, the two subtypes of aMCI might demonstrate differential thickness decrease patterns in certain cortical regions ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The selected nearest neighbouring samples to an individual 𝑖 are used to build a PSNN model through the following steps using the NeuCube SNN architecture [5]:…”
Section: Predictive Personalised Spiking Neural Network (Psnn) Modelmentioning
confidence: 99%
“…The classification accuracy was also compared with traditional methods: Multiple Linear Regression (MLR), Support Vector Machine (SVM), Multi-Layer Perceptron (MLP) and Evolving Clustering Method (ECM) [51] as shown in Table 2. The SVM optimal parameters that resulted in the best classification accuracy were found after performing the experiments several times with different parameter setting (polynomial degree within [2,5] and (RBF) kernel degree within [0.2, 1]). As shown in Table 2, when we used SVM for classification, the best accuracy was obtained using Kernel polynomial degree: 2.…”
Section: Case Study 1: Classification Based On Static Clinical Data and Spatiotemporal Eeg Data Related To Individual Response To Treatmementioning
confidence: 99%
See 1 more Smart Citation